2006
DOI: 10.1158/1055-9965.epi-06-0144
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Ki-ras Proto-oncogene Mutation and p53 Gene Overexpression in Sporadic Colorectal Adenomas with Demographic and Clinicopathologic Characteristics

Abstract: In colorectal tumorigenesis, Ki-ras proto-oncogene mutation often occurs early in the adenoma-adenocarcinoma sequence, whereas mutation of the p53 gene is associated with late progression to carcinoma. We evaluated the relationship of demographic and clinicopathologic characteristics to Ki-ras mutation and p53 gene product overexpression in 1,093 baseline sporadic colorectal adenomas from 926 individuals enrolled in a phase III recurrence prevention trial. Ki-ras mutation was found in 14.7% of individuals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 62 publications
2
24
1
Order By: Relevance
“…Meanwhile, other reports revealed these differences between the colon and rectum (Frattini et al, 2004;Kim et al, 2006). Also regarding K-ras/BRAF mutations, several reports have shown a higher prevalence of K-ras mutation in the rectum than in the colon (Luchtenborg et al, 2005;Barry et al, 2006;Einspahr et al, 2006), while other reports compared K-ras mutation between the proximal colon and the distal colon, and found dominance in the former (Samowitz et al, 2000;Miranda et al, 2006). BRAF mutation is also known to be associated with the proximal localisation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other reports revealed these differences between the colon and rectum (Frattini et al, 2004;Kim et al, 2006). Also regarding K-ras/BRAF mutations, several reports have shown a higher prevalence of K-ras mutation in the rectum than in the colon (Luchtenborg et al, 2005;Barry et al, 2006;Einspahr et al, 2006), while other reports compared K-ras mutation between the proximal colon and the distal colon, and found dominance in the former (Samowitz et al, 2000;Miranda et al, 2006). BRAF mutation is also known to be associated with the proximal localisation .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of K-ras mutation in adenomas was found to be lower (3 -17%) than that of CRCs, and the mutation had a strong association with larger adenoma size, villous histology, and high-grade dysplasia (Maltzman et al, 2001;Barry et al, 2006;Einspahr et al, 2006). In addition, our previous report indicated that the laterally spreading type of adenomas, particularly in the proximal colon, frequently carried the K-ras mutation (Hiraoka et al, 2006).…”
mentioning
confidence: 88%
“…The pathways that were specifically enriched in adenomas in our analysis are known to be activated in colorectal carcinogenesis (causal, resulting or compensatory) such as the Wnt pathway (Midgley and Kerr, 1999), cell cycle routes (Hao et al, 1998), DNA base metabolism, transcription, ATM (Kwong et al, 2008;Paulson et al, 2008), ARF, p27 (Payne et al, 2008) and p53 (Einspahr et al, 2006) signaling routes. In addition, we found novel pathways unique to adenomas, among which are the Rb pathway, the Src pathway, folate biosynthesis and the PTC1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is among the earliest genetic events of the process (51) although it is well known that it can occur at any stage (52). Its mutations are present in 50-95% of dysplastic ACF (34,53), in 15-78% of colorectal adenomas (54,55) and in 36-42% of CRCs (56). K-ras mutations on codons 12/13 of exon 2 and on codon 61 of exon 3 are de novo mutations whose presence depends on the random "activation" of the protooncogene K-ras during the life-span of healthy individuals either due to carcinogen exposure or to sporadic replication errors (57).…”
Section: Why Is K-ras Mutation a Potential Alternative Initiating Evementioning
confidence: 99%
“…People with benign colorectal polyps are "obliged" to undergo frequent follow-up colonoscopies, in order to have detected and eradicated possible index benign polyps, since every adenoma, serrated or not, has the capacity for malignant transformation (54,92). This strategy results in unnecessary colonoscopies; most adenomas don't progress to cancer (54), (the conversion rate is below 5%) (50), whilst a great gap is evident between the incidence of polyps (approximately 40%) (93) and that of CRC (nearly 6%) (1,4).…”
Section: Why Detecting K-ras Mutation In the Non-cancerous Colorectalmentioning
confidence: 99%